A Comparative Study of the Effects of Distance Learning and Face-to-Face Learning during the COVID-19 Pandemic on Learning Mathematical Concepts in Primary Students of the Kingdom of Bahrain - Mansour Saleh Alabdulaziz; Enas Anwar Tayfour (MDPI AG, 2023)
The main objective of this study is to compare the effectiveness of face-to-face learning and distance learning in helping fourth-grade primary students learn mathematical concepts. The data were collected from 120 fourth-grade students selected purposively and divided into two groups: a control group comprising 60 students, who used a face-to-face programme in their third grade, and an experimental group comprising 60 students, who used a distance learning programme in their third grade. A diagnostic test was used to measure their understanding of previous mathematical concepts. The current research revealed two interesting results: First, there were no statistically significant differences (p-value < 0.05) in rounding and ordering numbers, space concept, perimeter concept, and graphs between the face-to-face mode and distance learning mode, where students' results were almost similar. Second, there were statistically significant differences (p-value < 0.05) in the concepts of expanding pictures of numbers (verbal, analytic, and standard), compare numbers, basic arithmetic operations, units of measurement, geometric shapes, sides, and data visualisation in favour of the group of students who were taught in a face-to-face learning mode.